The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2008
DOI: 10.1021/es703144k
|View full text |Cite
|
Sign up to set email alerts
|

An Assessment of Fecal Indicator Bacteria-Based Water Quality Standards

Abstract: Fecal indicator bacteria (FIB) are commonly used to assess the threat of pathogen contamination in coastal and inland waters. Unlike most measures of pollutant levels however, FIB concentration metrics, such as most probable number (MPN) and colony-forming units (CFU), are not direct measures of the true in situ concentration distribution. Therefore, there is the potential for inconsistencies among model and sample-based water quality assessments, such as those used in the Total Maximum Daily Load (TMDL) progr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 39 publications
1
32
0
Order By: Relevance
“…Studies have shown that FIB survival in surface waters varies from hours to days or even months if protected by sediments which make identifying the source of the FIB concentrations difficult [37,38]. The decay rate of FIB in surface water is a function of many ecological influences; therefore, water quality management, best management plan (BMP) development, watershed modeling, and risk assessment practices need to incorporate better methods as to how FIB interact with the environment, and furthermore, how well FIB accurately model true pathogenic concentrations in the watershed [16,17]. Researchers and regulators continuously question which pathogen indicators are appropriate to determine safe exposure levels in recreational waters.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown that FIB survival in surface waters varies from hours to days or even months if protected by sediments which make identifying the source of the FIB concentrations difficult [37,38]. The decay rate of FIB in surface water is a function of many ecological influences; therefore, water quality management, best management plan (BMP) development, watershed modeling, and risk assessment practices need to incorporate better methods as to how FIB interact with the environment, and furthermore, how well FIB accurately model true pathogenic concentrations in the watershed [16,17]. Researchers and regulators continuously question which pathogen indicators are appropriate to determine safe exposure levels in recreational waters.…”
Section: Discussionmentioning
confidence: 99%
“…Current ambient water quality criteria for FIB in fresh waters are aimed to protect human health from gastroenteritis due to pathogenic exposure based on the estimated relative risk of 8 cases of gastroenteritis per 1000 swimmers [12]. The appropriateness of the methods used and FIB capability for correlating and identifying human health risk from pathogens has been debated in the literature [16][17][18][19]. Despite the ongoing debate, most states monitor for total coliforms, fecal coliforms, Escherichia coli (E. coli), fecal streptococci, or enterococci as indicators of potential pathogens in water resources.…”
Section: Introductionmentioning
confidence: 99%
“…Dissolved oxygen (30,54,57), chlorophyll (6,20,31,33), and plankton (2,31,41,59,74) have also been found to be important in the ecology of vibrios. Regulatory authorities responsible for oversight of recreational waters and shellfish harvesting areas employ rainfall, fecal coliform counts, river stages, and, more recently, enterococcus counts to determine opening and closing of specific areas to protect public health (21,25,62,76). Standard microbiological approaches to classification and opening/closing of oyster harvest areas, which are unfortunately not useful for control of exposure to pathogenic Vibrio spp., continue to be used and are generally accepted for regulating exposure to other pathogens in the United States (36).…”
mentioning
confidence: 99%
“…E. coli was selected as a standard non-human specific indicator of fecal contamination, though the limitations of this indicator are well-established. [66][67][68] In order to better characterise human fecal contamination of the household environment, V. cholerae and Shigella spp. were selected based on prevalence in southern Asia, evidence of public health importance, and field laboratory limitations.…”
Section: Environmental Enteric Dysfunctionmentioning
confidence: 99%